Depicting a Sámi Society Between Tradition and Modernization: The Strategies of Coping in Jovnna-Ánde Vest’s Trilogy Árbbolaccat - Fredriksen, Lill Tove (Nordlit, 2008)
The Sámi novelist Jovnna-Ánde Vest has written the trilogy Árbbolaččat, where he writes about the lives of the people living in Máhtebáiki, a small Sámi village in Northern Finland, from the late 1950s until the early 1980s. This is a time when new great changes coming from the majority society also has impact on the living conditions in a society where agriculture and fishing are the main lines of work. The article focuses on the protagonist Heaika and how he interacts and what kind of coping strategies he chooses in his endeavor to become a writer. Heaika serves both as a witness and a mediator of how the characters in the local society meet the impacts of the new time